COVID-19: Transportation and Tashkent State Agrarian University - Sulaymonov, Botirjon; Islamov, Sokhib; Abduvasikov, Abduaziz; Namozov, Normamat (Journal of Sustainability Perspectives, 2022)
The outbreak of COVID-19 pandemic has considerably and negatively affected the global community. To restrain the transmission of viruses, a restricted mobility has been highly imposed across the world and Uzbekistan as well. Our paper which responds to one of the directions of UI GreenMetric University Rankings provides a novel dataset on attitude-behaviors and personal perceptions of university students and academic staff in the term of transportation collected after the severe quarantine regime within the COVID-19 outbreak in Uzbekistan. We formulated a questionnaire design hinged on employing qualitative virtual interview and a short survey with students and university staff, estimating the sensitivity toward the potential crisis in crucially deciding on daily routines with restricted transportation and future mobility modes in the company of an urgent health concern. An online survey was distributed through Internet platforms such as Telegram within the period April-May 2020, with a total of 600 students, while a Zoom interview was organized for 50 of academic staff of Tashkent State Agrarian University. Our dataset comprises 362 out of 600 valid and full responses from students. Our survey was split into two sections. The first one has characterized the using frequency of all transportation modes before and after restricting the mobility, whereas the second section has considered potential risks of contracting COVID-19 from multi-modal transportation and potential effectiveness of travel mitigation measures. In general, the dataset was conveniently used to quantify and investigate students’ and staff’s attitude behavior towards traveling options and modal shifts due to COVID-19. Aligning with descriptive statistics, our paper also shares the results of possible explanatory emission calculations in transportation, serving as a reasonable reference for future studies during the pandemic.Keyword: Multimodal transportation, attitude-behavior, COVID-19, questionnaire, interview, emission, Uzbekistan